2022
DOI: 10.1007/s11096-022-01520-6
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and pooled prevalence of burnout in pharmacists

Abstract: Background Burnout is an occupational phenomenon caused by ineffectively managed work-related stress. Burnout is common among healthcare professionals and has the capacity to compromise patient care, but is not well characterised in pharmacists. Aim This systematic review aimed to establish the prevalence of burnout among pharmacists, and its associated risk factors. Method A systematic search of Embase, PubMed, CINAHL and PsychInfo was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 43 publications
0
21
0
2
Order By: Relevance
“…3,5 A 2022 systematic review across 8 countries estimated that 51% of pharmacists experience burnout. 3 In Canada, survey responses indicated that 79% of pharmacy professionals were at risk of burnout in 2023, a decrease from 92% in 2022, but a number that indicates burnout is still alarmingly widespread. 5 What is particularly concerning for the future of pharmacy is that younger ages are strongly correlated with worse mental…”
Section: Consequencesmentioning
confidence: 99%
See 3 more Smart Citations
“…3,5 A 2022 systematic review across 8 countries estimated that 51% of pharmacists experience burnout. 3 In Canada, survey responses indicated that 79% of pharmacy professionals were at risk of burnout in 2023, a decrease from 92% in 2022, but a number that indicates burnout is still alarmingly widespread. 5 What is particularly concerning for the future of pharmacy is that younger ages are strongly correlated with worse mental…”
Section: Consequencesmentioning
confidence: 99%
“…A potential reason for widespread pessimism is the prevalence of burnout, recognized as an occupational phenomenon caused by ineffective management of chronic stress. 3 Burnout is associated with increased job turnover and decreased psychological and physical well-being, leading to an increase in medication errors and reduced quality of care. 3 Understanding the factors contributing to burnout is essential if patient care is to be upheld as a core principle for pharmacy practice.…”
Section: Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Burnout is prevalent in a variety of jobs. In particular, the pooled prevalence of burnout in 43.2% in physicians, 4 in nurses is 11.2%, 5 in pharmacists is 51%, 6 in general practitioners is 37%, 7 in dentists is 13%, 8 in psychiatrists is 25.9%, 9 and in primary healthcare professionals is 28.1% 10 . We should notice that there are significant differences in prevalence of burnout between geographical regions, clinical settings and specialties.…”
Section: Introductionmentioning
confidence: 98%